Makna Sedekah Bumi Pada Masyarakat Transmigran Jawa di Kecamatan Sematujaya Kabupaten Lamandau Kalimantan Tengah - Lutfi Fauzi, M. Zainuddin (Journal Ilmu Sosial, Politik dan Pemerintahan, 2022)
This article aims to discusses Johan Galtung's perspective in analyzing the conflict that occurred between the Madura and Malay ethnic groups in Sambas through the concept of violence. The conflict has been seen as a natural process in community life with the cultural, religious, and ideological elements involved. The conflict in 1999 between Madura and Malay in Sambas regency happened sporadically and formed into violence. The conflict is constructed as negativity and an unwanted event. Theorists see that conflict can be understood as both a positive and a negative thing. Johan Galtung is one of the theorists who see a conflict with multidisciplinary analysis. He introduced the violence concept in three dimensions: structural violence, direct violence, and cultural violence. This article uses the qualitative method with a descriptive approach through textual reality analysis and literature review.